Effect of progesterone concentration on hCG trigger day on clinical outcomes after high-quality single blastocyst transfer in GnRH antagonist cycles - Jia, Nan; Xu, Jianing; Song, Bingbing; Hao, Haoying; Li, Meng; Zhang, Cuilian; Zhang, Shaodi (Frontiers in Medicine, 2024)
Objective To investigate whether progesterone levels on the human chorionic gonadotropin (hCG) trigger day are associated with clinical outcomes in fresh cycles and the first frozen–thawed cycles (the freeze-all strategy) following the transfer of a high-quality single blastocyst. Methods This single-center retrospective analysis was conducted on patients undergoing in vitro fertilization with the gonadotropin-releasing hormone (GnRH) antagonist protocol from January 2017 to December 2023. The study included the first and second oocyte retrieval cycles with progesterone levels ≤2 ng/ml on hCG trigger day. Clinical pregnancy rates and early miscarriage rates were compared among groups using curve fitting, threshold effect analysis, and multivariable regression. Results When progesterone levels were between 1 and 2 ng/ml, the pregnancy rate in fresh cycles was only 51% of that in cycles with progesterone levels ≤1 ng/ml (95% CI: 0.33, 0.79, p = 0.0028). And the pregnancy rate decreased by 25% (95% CI: 0.51, 1.09) for frozen cycles, although there was no statistically significant (p = 0.1273). When cycle types were used as a binary variable in multivariate regression analysis, it was found that the clinical pregnancy rate in frozen cycles was 1.84 times higher than in fresh cycles (OR = 1.84, 95% CI: 1.38–2.47). For progesterone levels between 1 and 2 ng/ml, the clinical pregnancy rate in frozen cycles was 2.90 times that of fresh cycles (OR = 2.90, 95% CI: 1.59, 5.29, p = 0.0015). Progesterone levels on hCG day had no impact on the clinical pregnancy rate in thaw cycles, nor did they affect miscarriage rates in fresh or thaw cycles (p > 0.05). Conclusion When progesterone levels on hCG trigger day were between 1 and 2 ng/ml, the clinical pregnancy rate for frozen–thawed cycles of high-quality single blastocyst transfer using an GnRH antagonist protocol significantly surpasses that of fresh cycles, thus elective frozen embryo transfer after the freeze-all strategy is recommended.